Dark Matter Registration in Ultraviolet, Visible, Infrared and Microwave Emission Spectrum Followed by Detailed Theoretical Background - Ivanov, Mikhail; Malakhov, Yury; Mamaev, Vadim; Saveliev, Grigory (Physics of Entropy, Radiation and Gravitating Matter with Examples of General and Analytical Solutions, 2021)
Experimental results of Dark Matter registration for various ranges of emission spectrum are presented as follows: in the ultraviolet range– for low velocity plasma jet, in the Dragon (Draco – in Latin) constellation (according to results obtained using the Hubble telescope) and in neighborhood of the Sun; in the visible range - in the case of sonoluminescence, during supersonic flow of a fighter and radiation of strong shock waves, as well as while studying molecules and atoms; in the infrared range - emitted by some land objects and thermal radiation; in the microwave range - as cosmic background radiation etc. We registered continuous spectrum of Dark Matter radiation mostly. Possible theoretical underpinning of our experimental results based on the DM modeling is also presented. Besides, we can simulate discrete spectrum in Dark Matter and with a view to confirm this we present the Fraunhofer C, F, G', and h lines corresponding to the alpha, beta, gamma and delta lines of the Balmer series for the hydrogen atom emission.